Mit i oralność w świetle diagnoz kryzysu kultury nowoczesnej - Rolka, Malwina (Hybris, 2016)
A category of secondary orality appeared in debate over the condition of contemporary culture by dint of Walter Jackson Ong’s research on influence of technology of word over an awareness of western man. Its concept designates a specific type of communicational situation, which is created by a twentieth-century ways of transmission of informations, like radio, television, telephone and another electronic voice-devices. In Ong’s works the perspective of secondary orality functions in context of the model of Greek culture, which preceded a beginning of the characterstic type of mentality, connected with the interiorization of script. The original oral awareness was dipped in world of mythical stories, which was created a cultural identity by dint of the acts of memorization and oral transmission of poetic experience. Analogies and differences between secondary and primary orality tease to ask about function and understanding the category of myth in perspective the first of them, which didn't appear in Ong’s works. A response to this question must connect with consideration of understanding the myth in contemporary reflection about the culture and with a search of symptoms of its presence in middle-class and consumerist societies, in which have appeared the technology of secondary orality. In my paper I'd like to try to recreate this elements of cultural background of contemporariness, which relate the age of twentieth-century orality to its ancient mythical grounding but equally indulge in transformations by dint of evolution of human condition in western culture.